2017
DOI: 10.1590/1981-6723.1316
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento e avaliação sensorial de goiaba-passa desidratada osmoticamente

Abstract: Este é um artigo publicado em acesso aberto (Open Access) sob a licença Creative Commons Attribution, que permite uso, distribuição e reprodução em qualquer meio, sem restrições desde que o trabalho original seja corretamente citado. Desenvolvimento e avaliação sensorial de goiaba-passa desidratada osmoticamente Development and sensory evaluation of osmotically dehydrated guava ResumoApesar de ser um fruto disponível durante todo o ano, nas regiões de cultivo irrigado das diferentes regiões do país, a goiaba a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
2
1
0
1
Order By: Relevance
“…In the Pareto diagram for solids gain, it is observed that the regression of the factors was significant at 95% confidence, with the concentration of sucrose being the parameter of greatest influence on the increase of this variable during osmotic dehydration, followed by the interaction between variables and temperature. The evaluated data corroborate the study carried out by Castro et al (2018), who also observed that sucrose concentration was the variable with the greatest influence on the incorporation of solids in fruits. Table 6 shows the equations of the linear models for the response variables, obtained during ISSN 2166-0379 2020 osmotic dehydration for the banana peel slices, under the different conditions of sucrose (X) and temperature (Y).…”
Section: Journal Of Agricultural Studiessupporting
confidence: 89%
See 1 more Smart Citation
“…In the Pareto diagram for solids gain, it is observed that the regression of the factors was significant at 95% confidence, with the concentration of sucrose being the parameter of greatest influence on the increase of this variable during osmotic dehydration, followed by the interaction between variables and temperature. The evaluated data corroborate the study carried out by Castro et al (2018), who also observed that sucrose concentration was the variable with the greatest influence on the incorporation of solids in fruits. Table 6 shows the equations of the linear models for the response variables, obtained during ISSN 2166-0379 2020 osmotic dehydration for the banana peel slices, under the different conditions of sucrose (X) and temperature (Y).…”
Section: Journal Of Agricultural Studiessupporting
confidence: 89%
“…Examining factorial design, it is observed that the concentration of sucrose is the variable that has the most influence in increasing this parameter. Likewise, Castro et al (2018), during the study of the development and sensory evaluation of osmotically dehydrated raisin guava, observed that the values of solids gains increased with the elevation of the temperature and mainly with the concentration of sucrose. Table 5 shows the analysis of variance (ANOVA) applied to the regression of the data of the osmotic dehydration response variables: WL, ML and SG to a linear model and their respective determination coefficients R 2 .…”
Section: Journal Of Agricultural Studiesmentioning
confidence: 96%
“…High moisture loss and solids gainrates in the early hours of theosmotic dehydrationprocesso of guava were reported by Castro et al [32]. Similar results were found by Silva et al [33], when studying the osmotic dehydration of acerola.…”
supporting
confidence: 84%
“…Tais características podem ter impulsionado pesquisas relacionadas à elaboração e caracterização de licores a base de frutas nacionais, como o camu-camu, açaí e caju (Viera, et al, 2010;Oliveira e Santos, 2011;Pina, 2014). Quanto à goiaba Paluma, há trabalhos científicos que tratam o processamento de néctar e bebida fermentada, efeitos do uso de atmosfera e embalagens modificadas e aumento de vida útil por desidratação osmótica (Corrêa, 2002;Brackmann et al, 2012;Lunguinho et al, 2014;Bertagnolli et al, 2017;Castro et al, 2018;), porém, percebe-se a carência de pesquisas associadas ao licor de goiaba.…”
Section: Introductionunclassified